Agenda-setting dynamics in the post-2020 cohesion policy reform: the pathway towards the European cross-border mechanism as possible policy change. Issue 7 (2nd October 2020) - Engl, Alice; Evrard, Estelle
ABSTRACT: Cross-border areas in Europe are promoted as places of integration, whose cooperation is encouraged by the Interreg programme and the European Grouping for Territorial Cooperation (EGTC) tool. For the 2021–2027 Cohesion Pack, the European Commission proposed the European Cross-Border Mechanism (ECBM), a regulation that would allow one member state to apply the law of a neighbouring member state to facilitate cross-border projects. This mechanism represents a paradigm shift, empowering border areas to manage their own integration (functional-horizontal) and institutionalise a policy pathway for resolving border-specific legal or administrative obstacles (institutional-vertical). This paper analyses the dynamics behind the ECBM proposal according to the multiple streams framework (MSF), revealing policy and politics streams' elements to explain agenda setting in EU policy processes. Methodologically, we apply a document analysis with qualitative content and cross-case analysis elements, and a combined strategy of deductive-inductive codes. This analysis is complemented and validated by expert interviews.